Beyond Panic: Variation in the Legislative Activity for Sex Offender Registration and Notification Laws Across States Over Time. (April 2019) - Lytle, Robert
Nationwide moral panic has long served as a primary explanation for sex offense laws. These laws, however, remain primarily left to state legislatures, which implies potential variation in their content over time. Variation in legislative content, to the degree that it represents implementation, not only suggests differential consequences for registrants and communities, but also it would raise questions to the sufficiency of moral panic as a sole explanation for sex offense policy change. I build upon earlier work by exploring variation in the content and timing of sex offender registration and notification (SORN) reform in all 50 states over time. After documenting variation in these laws, I present the ways in which SORN legislative content has evolved differently across states. In addition, the timing of legislative reforms differed not only across states but also within states over time. These findings have implications for existing theoretical assertions regarding criminal justice policy.